FAKTOR YANG BEHUBUNGAN DENGAN KEPATUHAN PENERAPAN PASIEN SAFETY PERAWAT DI RUMAH SAKIT HATIVE PASSO - Harianti Fajar; Elisabet Kundalim (Pasapua Health Journal, 2022)
Introduction: Patient safety is a process carried out by organizations that aims to make services to patients safer. The process includes risk assessment, identification and management of patient risk, reporting and analysis of incidents, and the ability to learn from a situation or event, follow up on an incident, and implement appropriate solutions to reduce the risk of it happening again. Method: This research is a type of analytic observational research using a cross sectional approach. The research sample was the nurses who served in the inpatient installation of Hative Passo Hospital, totaling 38 nurses. Data analysis was performed using univariate, bivariate and multivariate statistical tests (logistic regression). Results: Shows that there is no relationship between age and nurse compliance in implementing patient safety at Hative Passo Hospital, with a significance value. ρ value = 0.239 > α (0.050). There is a significant relationship between gender and nurse compliance in implementing patient safety at Hative Passo Hospital, with a significance value of ρ value = 0.011 <α (0.050). There is a significant relationship between education and nurse compliance in implementing patient safety at Hative Passo Hospital, with a significance value of ρ value = 0.006 <α (0.050). There is a significant relationship between length of service and nurse compliance in implementing patient safety at Hative Passo Hospital, with a significance value of ρ value = 0.001 <α (0.050). The educational variable is the variable that has the most role in the implementation of patient safety at Hative Passo Hospital. Conclusion: There is a relationship between gender, education, and years of service with the application of patient safety at Hative Passo Hospital.